2024 한국형 범불안장애 치료지침 II: 정신치료전략 - 박천일; 서준호; 김민경; 안명희; 이현아; 장윤영; 문은수; 이경욱; 서호석; 김원; Chun Il Park; Jun Ho Seo; et al. (Anxiety and mood, 2024)
Objective : This study aimed to establish a consensus on treatment strategies for psychological therapy in generalized anxiety disorder (GAD) as outlined in the 2024 Korean guidelines for treating GAD. Methods : The executive committee developed questionnaires on treatment strategies for patients with GAD based on previous treatment guidelines and academic articles published internationally and in Korea. Sixty-two experts responded to questionnaires developed. The consensus of expert opinions was classified into three categories (first-line, second-line, and third-line choices) using chi-square test and 95% confidence intervals. Results : Findings of this study suggest that individual cognitive behavioral therapy (CBT), group CBT, mindfulness-based cognitive therapy (MBCT), acceptance and commitment therapy (ACT), and applied relaxation are appropriate psychotherapies for GAD. Additionally, it is recommended to initiate CBT early when treating GAD, with eight treatment sessions being the most preferred for both individual and group CBT. Conclusion : This expert consensus survey reflected clinical experiences of Korean practitioners. Results of this study provide valuable insights for Korean clinicians when implementing psychotherapy for GAD.